Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1161/circimaging.112.977348
|View full text |Cite
|
Sign up to set email alerts
|

Association of Myocardial Deformation With Outcome in Asymptomatic Aortic Stenosis With Normal Ejection Fraction

Abstract: Background-Current guidelines recommend intervention for symptomatic aortic stenosis, but the management of asymptomatic aortic stenosis remains controversial. As left ventricular global longitudinal strain (GLS) has been shown to predict cardiovascular outcome, we sought to find whether its use could guide the assessment of risk in these patients. Methods and Results-We prospectively followed 79 patients with severe asymptomatic aortic stenosis (39 men; mean age, 77 ± 12 years; aortic valve [AV] area index, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(107 citation statements)
references
References 37 publications
5
97
1
4
Order By: Relevance
“…In a recent publication, we demonstrated that reduced longitudinal LV function was associated with a poor postoperative outcome in patients with AS and LVEF≥40% undergoing AVR. 15 Similar findings have since been demonstrated in asymptomatic patients with AS 16 and AS patients with LVEF≥50%. 17 The findings from these small cohort studies have been attributed to the improved ability of global longitudinal strain in detecting early stages of LV systolic impairment, as reduced longitudinal function is known to precede reduced circumferential function.…”
Section: Discussionsupporting
confidence: 68%
“…In a recent publication, we demonstrated that reduced longitudinal LV function was associated with a poor postoperative outcome in patients with AS and LVEF≥40% undergoing AVR. 15 Similar findings have since been demonstrated in asymptomatic patients with AS 16 and AS patients with LVEF≥50%. 17 The findings from these small cohort studies have been attributed to the improved ability of global longitudinal strain in detecting early stages of LV systolic impairment, as reduced longitudinal function is known to precede reduced circumferential function.…”
Section: Discussionsupporting
confidence: 68%
“…6,13,14 Patients were also categorized as having an LV global longitudinal strain ≤-15% or >-15%. 7, [15][16][17] The end-point of the study was all-cause mortality. All patients were followed-up after AVR.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, objective and reproducible parameters that identify early LV dysfunction, before a drop in LVEF could potentially allow more appropriate timing of surgery and in turn, allow improved survival. Over the past decade, the relationship between global LV load and abnormal LV systolic performance in AS patients, even in those with preserved LVEF has become more apparent, and the use of novel echocardiographic measures of LV load (Zva)19, 20, 45 and LV systolic performance (LV‐GLS)18, 30, 46 have been proposed as potential markers of early dysfunction, providing incremental prognostic utility.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exercise‐induced drop in systolic blood pressure is a Class IIa indication for surgery1, 2 However, these recommendations are based upon multiple small reports with heterogeneous end points3, 9, 10, 11, 12, 13, 14, 15 In a recent study, we have demonstrated that in asymptomatic patients with severe AS and preserved left ventricular ejection fraction (LVEF), only 50% achieved 100% of age‐sex predicted exercise capacity; with exercise stress testing providing significant reclassification of longer‐term mortality risk16 In the past decade, novel echo parameters including reduced left ventricular global longitudinal strain (LV‐GLS)17, 18, 19 and valvuloarterial impedance (Zva)17, 19, 20 have also been associated with worse prognosis in patients with asymptomatic severe AS. However, no study has systematically evaluated the incremental prognostic impact of resting Zva and LV‐GLS on data obtained from exercise stress testing in patients with asymptomatic severe AS and preserved LVEF.…”
Section: Introductionmentioning
confidence: 99%